Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1) Ta có a2 + b2 + c2 = ab + bc + ca
=> 2a2 + 2b2 + 2c2 = 2ab + 2bc + 2ca
=> 2a2 + 2b2 + 2c2 - 2ab - 2bc - 2ca = 0
=> (a2 - 2ab + b2) + (b2 - 2bc + c2) + (a2 - 2ac + c2) = 0
=> (a - b)2 + (b - c)2 + (a - c)2 = 0
=> \(\hept{\begin{cases}a-b=0\\b-c=0\\a-c=0\end{cases}}\Rightarrow\hept{\begin{cases}a=b\\b=c\\a=c\end{cases}}\Rightarrow a=b=c\left(\text{đpcm}\right)\)
a^2 + b^2 + c^2 = ab + bc + ca
<=> 2a^2 + 2b^2 + 2c^2 - 2ab - 2ac - 2bc = 0
<=> (a-b)^2 + (b-c)^2 + (c-a)^2 = 0
<=> a-b = 0 và b-c=0 và c-a=0
<=> a=b=c
a^2/b+c + b^2/a+c + c^2=a+b
= a(a/b+c) + b(b/a+c) + c(c/a+b)
= a(a/b+c + 1 - 1) + b(b/a+c + 1 - 1) + c(c/a+b + 1 - 1)
= a(a+b+c/b+c) - a + b(a+b+c/a+c) - b + c(a+b+c/a+b) - c
= (a+b+c)(a/b+c + b/a+c + c/a+b) - (A+b+c)
mà a/b+c + b/a+c + c/a+b = 1
= a+b+c - (a+b+c)
= 0
Câu 4 :
Ta có : a+b+c=0
=> a+b=-c
Lại có : a3+b3=(a+b)3-3ab(a+b)
=> a3+b3+c3=(a+b)3-3ab(a+b)+c3
=-c3-3ab. (-c)+c3
=3abc
Vậy a3+b3+c3=3abc với a+b+c=0